2, 3‐Pentandion [MAK Value Documentation in German language, 2017]. Issue 1 (26th January 2017) - Hartwig, Andrea; ,
2, 3‐Pentanedione [pentane‐2, 3‐dione]: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has evaluated 2, 3‐pentanedione to derive a maximum concentration at the workplace (MAK value), considering all toxicity endpoints. The critical effects of 2, 3‐pentanedione were inflammation, necrosis, ulceration and fibrosis in the lung and inflammation, exudates and metaplasia in the nasal cavity in rats and mice after inhalation for 14 days. In this study the NOAEC in rats was 49 ml/m 3 and the LOAEC in mice was 49 ml/m 3 for effects in the lung. The occurrence of fibrosis after only two weeks of inhalation is assessed as a severe effect. Due to the structural similarity of 2, 3‐pentanedione to diacetyl (2, 3‐butanedione), which is responsible for bronchiolitis obliterans in popcorn workers, and the likeliness of lung effects in rodents, a MAK value of 0.02 ml/m 3 is set in analogy to diacetyl. As the critical effect is systemic, 2, 3‐pentanedione is assigned to Peak Limitation Category II. The excursion factor of 1 is set in analogy to diacetyl. Skin contact may contribute significantly to systemic toxicity and 2, 3‐pentanedione is designated with an "H". In analogy to diacetyl, skin sensitization (Sh) is expected but not airway sensitization. Because there are no studies on developmental toxicity, the substance is assigned to Pregnancy Risk Group D. 2, 3‐Pentanedione is neither genotoxic nor carcinogenic.